A novel grapevine badnavirus is associated with the Roditis leaf discoloration disease - Maliogka, Varvara; Olmos, Antonio; Pappi, Polyxeni G.; Lotos, Leonidas; Efthimiou, Konstantinos; Grammatikaki, Garyfalia; Candresse, Thierry; Katis, Nikolaos; Avgelis, Apostolos D. (2017)
Roditis leaf discoloration (RLD), a graft-transmissible disease of grapevine, was first reported in Greece in the 1980s. Even though various native grapevine viruses were identified in the affected vines, the etiology of the disease remained unknown. In the present study, we used an NGS platform for sequencing siRNAs from a twenty-year old Roditis vine showing typical RLD symptoms. Analysis of the NGS data revealed the presence of various known grapevine viruses and viroids as well as a hitherto uncharacterized DNA virus. The circular genome of the new virus was fully reassembled. It is 6988 nts long and includes 4 open reading frames (ORFs). ORF1, ORF2 and ORF4 code for proteins with unknown functions while ORF3 encodes a polyprotein with motifs related to the replication, encapsidation and movement of the virus. Phylogenetic analysis classified the novel virus within the genus Badnavirus, with closest relationship to Fig badnavirus 1. Further studies showed that the new badnavirus is closely related with the RLD disease and the provisional name grapevine Roditis leaf discoloration-associated virus (GRLDaV) is proposed. Our findings extend the number of DNA viruses identified in grapevine, further drawing attention to the potential importance of this virus group on grapevine pathology.